Evaporation and crystallization of saline droplet with surfactant on smooth surfaces - Fong, Jia Jin (Nanyang Technological University, 2021)
The evaporation and crystallization of saline droplets have been the subject of interest due to their potential in the pharmaceutical industry, where the process of drug formulation requires precise solute deposition control. The use of surfactant has proven helpful as it can modulate the droplet wettability and deposition control. Despite numerous contributions by researchers in this field, the understanding remains abstruse. This project experimentally investigated the evaporative and crystalline patterns from a sessile saline droplet with surfactant on a silicon wafer substrate. Salt and surfactant concentrations were varied in the solution to examine the effect of each component. When trace amount of surfactant is increased in the solution, an autophobic effect induced by surfactant was observed. An immediate de-pinning of the droplet and increased contact angle were observed, contradictory to what is expected, as surfactant should decrease surface tension, improving droplet wettability. However, further increase in surfactant leads to contact line pinning for the entire evaporation sequence of the droplet. The contact angle over time, crystalline deposit, time to crystallization, dendritic structures were sensitive to the surfactant concentration. With the surfactant concentration fixed, the salt concentration is increased in the solution. With the increase in salt concentration, the salt crystal cube grew larger as expected, with dendritic structures appearing near the contact line to be much thinner in size. At higher salt concentrations, no contact line motion was observed, the droplet undergoes constant contact radius throughout the entire evaporation sequence. Recommended future works can include visualizing the surfactant interplay with local surfaces to better understand the initial contact line motion and dendritic formations. Further study will enhance the relationship between surfactant adsorption and the phenomena mentioned above.